2018
DOI: 10.1186/s12913-018-3303-7
|View full text |Cite
|
Sign up to set email alerts
|

How U.S. children’s hospitals define population health: a qualitative, interview-based study

Abstract: BackgroundThe literature suggests that although adult hospitals are establishing population health programs around the country, there is considerable definitional ambiguity regarding whether interventions are aimed at the social determinants of health or the management of existing patient populations. U.S. children’s hospitals also undertake population health programs, but less is known about how they define population health. The purpose of this study is to understand how U.S. children’s hospitals define popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…For example, focusing efforts to improve population health only on patients may divert attention and resources away from more upstream interventions, like improving neighborhood conditions, that are needed to improve health across whole communities. A further distinction has therefore been made between “population health improvement” and “population health management”—the latter describing approaches to improve health that focus on defined groups of patients served by health plans, hospitals, ACOs, or other health care organizations, rather than the whole community living in a particular geographical area . Health care systems can—and sometimes do—pursue both strategies at the same time: they can focus on improving care for their patient populations while collaborating with other services and sectors to improve health for a wider geographic population .…”
Section: Terms and Distinctionsmentioning
confidence: 99%
“…For example, focusing efforts to improve population health only on patients may divert attention and resources away from more upstream interventions, like improving neighborhood conditions, that are needed to improve health across whole communities. A further distinction has therefore been made between “population health improvement” and “population health management”—the latter describing approaches to improve health that focus on defined groups of patients served by health plans, hospitals, ACOs, or other health care organizations, rather than the whole community living in a particular geographical area . Health care systems can—and sometimes do—pursue both strategies at the same time: they can focus on improving care for their patient populations while collaborating with other services and sectors to improve health for a wider geographic population .…”
Section: Terms and Distinctionsmentioning
confidence: 99%
“…A further distinction has therefore been made between "population health improvement" and "population health management"-the latter describing approaches to improve health that focus on defined groups of patients served by health plans, hospitals, ACOs, or other health care organizations, rather than the whole community living in a particular geographical area. 22 Health care systems can-and sometimes do-pursue both strategies at the same time: they can focus on improving care for their patient populations while collaborating with other services and sectors to improve health for a wider geographic population. 23 But the clear risk is that health care systems predominantly pursue more downstream interventions for their sickest and most expensive patients.…”
Section: Population Health Improvement and Population Health Managementmentioning
confidence: 99%
“…From this still developing literature, it is known that hospitals have faced barriers to adopting population health models, including building a rationale for increased expenditures on social supports and services that address nonmedical factors, developing metrics to demonstrate financial and population health impact, and cultivating trust among community members. 11,12 Still, there is evidence that hospitals are successfully engaging community-based partners to carry out population health work and that the ACA's new requirements have encouraged collaboration between hospitals, local communitybased organizations, and local health departments. 13,14 For example, a recent study found that the majority of public health departments are partnering with local hospitals to carry out Community Health Needs Assessments (CHNAs) and plan population health programming.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Hospitals also have partnered with a host of government and community-based organizations, including city planners, advocacy groups, local schools, social service agencies, providers of legal aid, and environmental groups. 12,18,19 Although the degree of collaboration and community input varies, 20 these studies suggest that partnerships may be essential to overcoming some of the barriers identified in adopting population health models within hospital organizations.…”
Section: Introductionmentioning
confidence: 99%